2019
DOI: 10.1002/aelm.201800688
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale, Low‐Power Nonvolatile Memory Based on Few‐Layer MoS2 and Ultrathin Polymer Dielectrics

Abstract: With the advent of artificial intelligence and the Internet of Things, demand has grown for flexible, low‐power, high‐density nonvolatile memory capable of handling vast amounts of information. Ultrathin‐layered 2D semiconductor materials such as molybdenum disulfide (MoS2) have considerable potential for flexible electronic device applications because of their unique physical properties. However, development of flexible MoS2‐based flash memory is challenging, as there is a lack of flexible dielectric material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…The ultrasmooth, ultrathin (3-15 nm), flexible, and crosslinked organosilicon layer, poly(2,4,6trivinyl-2,4,6-trimethyl cyclotrisiloxane) (PV3D3, dielectric constant, k~2.2), has been integrated into devices 80,81 , including 3D stacking of organic thin film transistors (TFTs) 82 . The PV3D3 serves as an electret layer when coupled with an ultrathin (20 nm) crosslinked iCVD poly(1,4butanediol diacrylate) (PBDDA) film as blocking dielectric (Fig.…”
Section: Organic and Hybrid Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultrasmooth, ultrathin (3-15 nm), flexible, and crosslinked organosilicon layer, poly(2,4,6trivinyl-2,4,6-trimethyl cyclotrisiloxane) (PV3D3, dielectric constant, k~2.2), has been integrated into devices 80,81 , including 3D stacking of organic thin film transistors (TFTs) 82 . The PV3D3 serves as an electret layer when coupled with an ultrathin (20 nm) crosslinked iCVD poly(1,4butanediol diacrylate) (PBDDA) film as blocking dielectric (Fig.…”
Section: Organic and Hybrid Devicesmentioning
confidence: 99%
“…86 For higher k dielectrics, the iCVD copolymerization of 2-cyanoethyl acrylate and the crosslinker DEGDVE achieved k~6.2. 81 Extension of the iCVD method for ultrathin, flexible, and high-k hybrid organic-inorganic layers for fabricating low-leakage current TFTs. 87,88 The hybrids were obtained by adding of trimethyl alumina or tetrakis-dimethyl-amino-zirconium reactant vapors along HEMA and the TBPO initiator.…”
Section: Organic and Hybrid Devicesmentioning
confidence: 99%
“…Inset shows the switching endurance for over 1500 cycles. Adapted with permission under a Creative Commons CC-BY License from ref . Copyright 2019 John Wiley and Sons.…”
Section: Electrostatic Control Of Atomically Thin Memory Devicesmentioning
confidence: 99%
“…Due to opportunities for simplified processing, researchers have also explored atomically thin nonvolatile memory where nanoscale metal films are evaporated and annealed to obtain metal islands or nanoparticles that act as floating gates. For example, Wang et al determined that Au nanoparticles, compared to Co, Ag, and Al, provided superior floating-gate performance with a voltage hysteresis of 10 V, switching ratio of 10 6 , and retention for over 2000 s in MoS 2 -based devices . Replacing the metal control gate with an indium tin oxide (ITO) gate, Gong et al demonstrated voltage hysteresis of 10 V with a switching ratio > 10 3 , where a laser pulse could promote carriers to the floating gate .…”
Section: Electrostatic Control Of Atomically Thin Memory Devicesmentioning
confidence: 99%
See 1 more Smart Citation